2017
DOI: 10.1016/j.diff.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The small GTPase Arf6 regulates sea urchin morphogenesis

Abstract: The small GTPase Arf6 is a conserved protein that is expressed in all metazoans. Arf6 remodels cytoskeletal actin and mediates membrane protein trafficking between the plasma membrane in its active form and endosomal compartments in its inactive form. While a rich knowledge exists for the cellular functions of Arf6, relatively little is known about its physiological role in development. This study examines the function of Arf6 in mediating cellular morphogenesis in early development. We dissect the function of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 83 publications
2
6
0
Order By: Relevance
“…A recent study in sea urchin primary mesenchyme cells showed that constitutively active Arf6 induced mislocalization of junctional cadherin ( Stepicheva et al, 2017 ). In C. elegans , apical junctions contain cadherin, HMP-1 (α-catenin), and HMP-2 (β-catenin; Cox and Hardin, 2004 ).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study in sea urchin primary mesenchyme cells showed that constitutively active Arf6 induced mislocalization of junctional cadherin ( Stepicheva et al, 2017 ). In C. elegans , apical junctions contain cadherin, HMP-1 (α-catenin), and HMP-2 (β-catenin; Cox and Hardin, 2004 ).…”
Section: Resultsmentioning
confidence: 99%
“…To examine the actin dynamics in control TP and Dvl miRNATP, we microinjected newly fertilized eggs with 500 ng mCherry-LifeAct reporter mRNA, 0.5 µl 100% glycerol and 0.5 µl of Texas Red in a 2.5 µl injection solution (Riedl et al, 2008;Stepicheva et al, 2017).…”
Section: Microinjectionsmentioning
confidence: 99%
“…Calcium bearing vesicles perform an active diffusion motion in the skeletogenic cells with a diffusion length that inversely correlates with the strength and activity of the actomyosin network [46]. Actin filaments are formed around the spicule [46, 47] and F-actin signal is enriched at the tips of the growing skeletal rods in skeletogenic cell culture [48]. Genetic and pharmacological perturbations of the GTPase, CDC42, prevent the formation of filopodia in the skeletogenic cells and inhibit spicule formation and elongation [49].…”
Section: Introductionmentioning
confidence: 99%